An investigation into the function and mechanism of a GRK5-L41 polymorphism using human pluripotent cell-derived cardiomyocytes - Vo, Nguyen T. N. (2021)
A single-nucleotide polymorphism (SNP) in G protein-coupled receptor kinase 5 (termed GRK5-Q41L) was reported to be associated with a low mortality rate for patients with heart failure and cardiac ischemia (Liggett et al., 2008). An in vitro study on transfected cells and transgenic mice suggested that this GRK5-Q41L polymorphism enhances β-adrenergic receptors (β-AR) desensitisation to prevent adverse effects of chronic β-AR stimulation.